A Quasi-Experimental Study of the Effects of the Erggi Action Model of Musculoskeletal Symptoms and VDU Working Conditions Among University Staff. - Tiainen, Sari; Ropponen, Annina; Louhevaara, Veikko (International Journal of Occupational Safety & Ergonomics, 2014)
Purpose. The aim of this study was to investigate musculoskeletal symptoms and working conditions of university workers with and without contact with an Erggi action model. Methods. A quasi-experimental and longitudinal field study design examined effects of the Erggi action model with 3 types of questionnaires filled by 1000 university workers. The statistical analyses used logistic regression. Results. Subjects who had contact with the Erggi action model had a higher probability of weekly musculoskeletal symptoms impairing their work, perceived more possibilities to influence their musculoskeletal symptoms and had lower risk for sick leave compared to those without contact with the Erggi action model. Conclusions. The Erggi action model increases the probability of influencing workers' musculoskeletal symptoms, decreases the number of sick leave and increases awareness of musculoskeletal symptoms and working conditions.